Pendampingan Academic Plenary Meeting untuk Meningkatkan Kemampuan Berbicara Bahasa Inggris Siswa SMA - Citrayasa, Vinindita; Marsella, Elisabeth (Proletarian : Community Service Development Journal, 2025)
The Academic Plenary Meeting (APM) activity, held regularly at SMA Pangudi Luhur (PL) Van Lith, aims to develop students’ English speaking skills as well as their soft skills, including critical thinking, creativity, and self-confidence. To ensure optimal outcomes, additional mentoring is required. This community service program was designed to provide such mentoring support. Using an experiential learning approach, the mentoring was conducted over ten sessions featuring English-speaking performances in various formats and themes, including argumentative speeches, discussions, debates, movie reviews, talk shows, and theatrical monologues. In this program, the facilitators’ roles included designing assessment rubrics, conducting assessments, and providing feedback. The students demonstrated efforts to deliver spontaneous performances, although improvement is still needed. Well-chosen topics and adequate preparation were also found to contribute to better performance in each session. For further improvement, students’ dependence on notes and the enhancement of gestures during performance need additional practice.